An Algorithm for Simulation of Waiting Systems with Different Types and Variable Number of Parallel Working Stations Each Having its Own Queue - Florea, Ion; Sasu, Lucian (ICI Bucharest, 2012)
This paper presents waiting systems with parallel working stations, for which both the clients and the working stations are grouped in classes. The working stations from the same class are identical and have their own waiting queues. The clients’ arrivals, the choice of a class to whom the client belongs to and furthermore the choice of the serving station relies on a random process. Also, this approach considers a variable number of stations, influenced by the number of clients in the system. For this kind of problems there is no suitable analytical method and the support offered by specialized languages is quite poor. The paper presents a study approach for this kind of systems, based on discrete event simulation. It is shown that the given algorithm has a polynomial complexity. Also, the object-oriented design we used for implementation is sketched.
Keywords: Queuing System; Waiting Queue; Simulation Algorithm; Polynomial Complexity; Different Classes of Stations; Variable Number of Active Stations